Life-threatening hypercalcaemia in association with Addisonian crisis. Issue 790 (August 1991) - Miell, J.; Wassif, W.; McGregor, A.; Butler, J.; Ross, R.
Abstract : A 35 year old woman was admitted with acute radial artery occlusion necessitating two operations and thrombolytic therapy. Subsequently a diagnosis of primary hypothyroidism was made and she was commenced on thyroxine replacement therapy. Her condition, however, continued to deteriorate with the development of an Addisonian crisis heralded by, and complicated by, severe, life-threatening hypercalcaemia. This case highlights the importance of considering Addison's disease in any patient whose condition deteriorates after the introduction of thyroxine replacement, and illustrates the often forgotten association of hypercalcaemia and hypoadrenalism.